ASCE 7-22 tornado provisions - Foster, Perry K. (Kansas State University, 2023)
The recently published ASCE 7-22 Minimum Design Loads and Associated criteria for Buildings and Other Structures added a new chapter (Chapter 32) for tornado provisions. In the past there have been many devastating tornados that have caused considerable damage and many casualties, but prior to the 2022 version there were no provisions in ASCE 7 addressing tornado effects. The provisions in Chapter 32 aim to provide design methods against tornado loads for buildings that pose a significant risk to life safety or are essential to survival (Risk Categories III and IV buildings). The new tornado design method is based on modifying current methods of wind design used in Chapter 26, 27 and 30 of the code for Main Wind Force Resisting Systems (MWFRS) and Component and Cladding (C&C) design. While the methodology is the same, there are many changes in the parameters and factors used for the actual calculations due to the unique nature of tornados. With the parametric changes there are also specifications for the envelope and the enclosure classification as well as requirements for openings. This report introduces the tornado provisions in Chapter 32 by highlighting the different parameters used in load calculation between tornado and regular wind. The impact to Risk Category III and IV buildings is illustrated by two building examples.
Keywords: Tornado; ASCE 7-22